Dampak Penggunaan Wifi Bersama terhadap Konflik Sosial Antar Warga di Lingkungan Permukiman - Hafizah; Devy, Tartila; Widianita, Rika; Ridhah, Habibatur; Anisah, Ariyun (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the impact of shared WiFi usage on social conflicts among residents in the Aur Kuning urban settlement, Bukittinggi City. This research employs a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation involving WiFi users, internet network owners, adolescents, and local community leaders. Data analysis follows the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings show that shared WiFi usage in Aur Kuning has triggered various social conflicts among residents, such as disputes over internet cost-sharing, late payment of contributions, excessive network usage, and reduced internet quality due to too many users. In addition, intensive internet use has decreased face-to-face social interaction, as residents tend to spend more time using mobile devices rather than engaging with their surroundings. Among adolescents, shared WiFi is predominantly used for online gaming and social media activities until late at night, which has caused disturbances to neighborhood comfort. This study concludes that shared WiFi usage not only provides benefits in supporting communication and information needs but also influences changes in urban community social relations. Therefore, supervision of internet use, effective communication among residents, and collective rules regarding WiFi usage are needed to minimize social conflicts in residential areas.ter Keywords: Wifi Usage, Social Conflict and Residential Environment